2015
DOI: 10.1088/1741-2560/12/6/066030
|View full text |Cite
|
Sign up to set email alerts
|

Use of probabilistic weights to enhance linear regression myoelectric control

Abstract: Objective Clinically available prostheses for transradial amputees do not allow simultaneous myoelectric control of degrees of freedom (DOFs). Linear regression methods can provide simultaneous myoelectric control, but frequently also result in difficulty with isolating individual DOFs when desired. This study evaluated the potential of using probabilistic estimates of categories of gross prosthesis movement, which are commonly used in classification-based myoelectric control, to enhance linear regression myoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…There is an extensive discussion in the literature about 59 performance of classifiers, with each having variable 60 number of amputees (trans-radial [43] or trans-humeral 61 [44], feature selection methods [45,46,47] (Figure 4), previous studies reported low performance up to 30% classification error [55]. In general, the performance of each classifier was similar to previously reported results [53,56]. Combined EMG was significantly better (P<0.05) than the surface and intramuscular EMG as a combined feature set improved the information level from muscles containing both local and global content.…”
Section: Discussion 58supporting
confidence: 80%
See 2 more Smart Citations
“…There is an extensive discussion in the literature about 59 performance of classifiers, with each having variable 60 number of amputees (trans-radial [43] or trans-humeral 61 [44], feature selection methods [45,46,47] (Figure 4), previous studies reported low performance up to 30% classification error [55]. In general, the performance of each classifier was similar to previously reported results [53,56]. Combined EMG was significantly better (P<0.05) than the surface and intramuscular EMG as a combined feature set improved the information level from muscles containing both local and global content.…”
Section: Discussion 58supporting
confidence: 80%
“…Intramuscular signals provide independent control sites that can enable simultaneous and proportional control of multiple DOF's [56]. The downside of this simultaneous and proportional control is past pointing, isolating 1 DOF targets and ballistic nature of movements during positioning [56,57].…”
Section: Discussion 58mentioning
confidence: 99%
See 1 more Smart Citation
“…To match the natural dexterity of the human hand, several groups have proposed using regression‐based algorithms or continuous methods . Unlike pattern recognition, regression algorithms can use the rate of change in neurological activity to continuously and simultaneously estimate multiple control signals.…”
Section: Control Methodsmentioning
confidence: 99%
“…Unlike pattern recognition, regression algorithms can use the rate of change in neurological activity to continuously and simultaneously estimate multiple control signals. Both peripheral nerve and brain interfaces have had success in implementing these algorithms for continuous control of multiple DoFs . Although these algorithms show promise in accelerating the progress toward natural arm and hand control, there still remain some limitations.…”
Section: Control Methodsmentioning
confidence: 99%